Concordance of "Case Level" Global, Highest, and Largest Volume Cancer Grade Group on Needle Biopsy Versus Grade Group on Radical Prostatectomy. (November 2018) - Trpkov, Kiril; Sangkhamanon, Sakkarn; Yilmaz, Asli; Medlicott, Shaun A.C.; Donnelly, Bryan; Gotto, Geoffrey; Shea-Budgell, Melissa
Abstract : The practice of assigning "case level" biopsy Grade Group (GG) or Gleason Score is variable. To our knowledge, a comparison of the concordance of different biopsy "case level" GG with the prostatectomy GG has not been done in a post-2005 prostate cancer cohort. We evaluated the GG in 2527 patients who had biopsy and radical prostatectomy performed at our institution between 2005 and 2014. We compared the agreements, the upgrades, and the downgrades of 3 different "case level" biopsy GG, with the final GG: (1) Global GG (sum of most prevalent and highest Gleason grade in any biopsy part/site-specific specimen); (2) Highest GG (found in any biopsy part/site-specific specimen); and (3) Largest Volume Cancer GG (found in any biopsy part/site-specific specimen). The concordance between the biopsy and the final GG were evaluated using weighted kappa (κ) coefficient. The biopsy Global GG, Highest GG, and Largest Volume Cancer GG were the same as the final GG in 60.4%, 57.1%, and 54.3% cases, respectively (weighted κ values: 0.49, 0.48, and 0.44, respectively). When final GG contained tertiary 5, the overall GG agreement decreased: Global GG 41.5%, Highest GG 40.3%, and Largest Volume Cancer GG 37.1% (weighted κ: 0.22, 0.21, and 0.18, respectively). A subset analysis for cases in which the biopsy Global GG and Highest GG were different (n=180) showed an agreement of 62.4% (weighted κ: 0.37) and 18.8% (weighted κ: 0.16), respectively. In patients without a tertiary Gleason pattern on radical prostatectomy, the Global GG and the Highest GG were identical in 92.4% of biopsies. Assigning a biopsy "case level" Global GG versus using the Highest GG and the Largest Volume Cancer GG resulted in comparable and slightly improved agreement with the final GG in this cohort. Abstract : Supplemental Digital Content is available in the text.